Kajian Terhadap Cabaran Pemilikan Harta Tanah oleh Generasi Y di Johor Bahru - Nurul Afiqah Mat Sidik; Omar, Abdul Jalil; Wan Yusoff, Wan Zahari; Shamsudin, Zarina; Eni, Sabariah (Research in Management of Technology and Business, 2021)
Buying a house is very important and is a big step in one’s life. Home ownership not only requires a high financial commitment but also a long-term investment. The issues and problems that arise in property ownership are that Generation Y is in a dilemma whether to rent or buy their first house. One of the reasons is that the price is beyond their eligibility that prevent the loan facility from the bank. The objective of this paper is to identify the challenges of property ownership by Generation Y. The paper also explores property marketing strategies by developers in accordance with the requirements of Generation Y. This study will use quantitative methods for both objectives. The study area is only concentrated in Johor Bahru, Johor with the total number of respondents is 89 respondents. Feedback from the results of this study was summarized using descriptive data. The results for this study found that Generation Y faces challenges in property ownership, especially in terms of their eligibility to secure financial facilities to buy their home. Based on the result, 88% respondents have agreed that the inability to buy a house according to the price in the market is their biggest challenge. In conclusion, property developers need to provide the facilities that suit with the needs of the Generation Y such as public and basic facilities.